The effect of influencer engagement rate in increasing followers of Instagram official account - Monacho, Benny Chandra; Slamet, Yulius (Penerbit Universiti Kebangsaan Malaysia, 2023)
The phenomenon of influencer marketing has grown rapidly in recent years. Instagram is considered one of the social media platforms that produce the highest number of influencer marketing, especially to reach Generation Y and Generation Z. Influencers are part of the marketing strategy, which is also used by brands to market their products. Several studies show that the engagement rate affects the desire to buy from followers of official Instagram accounts, and also make followers consider to buy products from the official Instagram account is the number of followers. Therefore, the main study of this research is to compare the effect of the engagement rate of Instagram influencers on increasing the number of followers of official brand accounts so that the resulting recommendations can be used in the next stage of the influencer marketing process. The research will be conducted using quantitative research methods. There are two types of variables, the dependent variable is the result of adding followers to the official account during the research period and the independent variable of this research is the engagement rate value of the influencer. The results show that the engagement rate of influencers has no effect on increasing followers on Instagram's official accounts, but the engagement rate value affects the percentage increase in the number of followers. This shows that the higher the engagement rate, the higher the percentage of additional followers. A significant increase 24.7 % in followers (account number) will occur on official accounts that have previously had more followers when doing influencer marketing.